EXPLORING BRAND POSITIONING AND HOTEL PERSONA TROUGH WOM AND CONTENT BY TEXT ANALYSIS - Tri Widarmanti; Gadang Ramantoko (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
Hotel management will concentrate on addressing difficult challenges and finding new ways for hotels to succeed in today's changing market world. Online customer reviews can be used to reflect the degree of differentiation between hotel brands and understanding the hotel industry's market structure through text analytics. The purpose of this study is to discover and demonstrate how customer online reviews (WOM and content), in the hospitality industry using text analysis can be used to explore brand positioning of hotel persona. This study gathered 4.215 online reviews one of hotel at Bandung city from year of 2015 – 2019, the methodology used the approach of text classification, quantitative analysis of text. This study found the category of visitors who stay the most are comes from family category and romantic vacation category, while the target visitors expected by the hotel are from business traveler’s category. Most customer state the word "family" when mentioning the hotel. Children, family, pool, zoo are the words most often discussed in customer reviews. This study findings can be used as an insight into what are the things that generate a satisfying experience and strengthen brand positioning of the hotel. In the future, it would be interesting to gathered data from multiple e-commerce application, and combining ontology-learning-based text mining and psychometric techniques to translate online hotel’s reviews into a hotel’s positioning map, capturing the relationship between product of hotel and reviewer effectively. Keywords: online review, brand positioning, text analytics, customer perceived value, hotel persona